An Investigation of Abadi and Cardelli's Untyped Calculus of Objects - Johannsen, Jacob (BRICS Report Series, 2008)
We study the relationship between the natural (big-step) semantics and the reduction (small-step) semantics of Abadi and Cardelli's untyped calculus of objects. By applying Danvy et al.'s functional correspondence to the natural semantics, we derive an abstract machine for this calculus, and by applying Danvy et al.'s syntactic correspondence to the reduction semantics, we also derive an abstract machines for this calculus. These two abstract machines are identical. The fact that the machines are identical, and the fact that they have been derived using meaning-preserving program transformations, entail that the derivation constitutes a proof of equivalence between natural semantics and the reduction semantics. The derivational nature of our proof contrasts with Abadi and Cardelli's soundness proof, which was carried out by pen and paper. We also note that the abstract machine is new. To move closer to actual language implementations, we reformulate the calculus to use explicit substitutions. The reformulated calculus is new. By applying the functional and syntactic correspondences to natural and reduction semantics of this new calculus, we again obtain two abstract machines. These two machines are also identical, and as such, they establish the equivalence of the natural semantics and the reduction semantics of the new calculus. Finally, we prove that the two abstract machines are strongly bisimilar. Therefore, the two calculi are computationally equivalent.